Competent consumer in the market for services (in the light of research) - Dąbrowska, Anna; Janoś-Kresło, Mirosława (Economic and Environmental Studies, 2020)
An aim of the article is to point out to behaviours of the Polish competent consumer in the market for services. The authors used the results of empirical research carried out for the purposes of the research project financed on funds of the National Science Centre entitled Consumers’ competencies as a stimulant of innovative behaviour and sustainable consumption, undertaken at the Institute for Market, Consumption and Business Cycles Research (IBRKK) in the years 2012-2014. The research findings showed that for the competent consumer the most important factors in the course of using services are, first of all, price and quality. More than half of the surveyed individuals declared they were reading the terms of the agreement being signed, in the case of noticed defect of the product or badly provided service they raise a claim and they also ask of the claim terms. Low also appeared to be consumers’ awareness of the familiarity with institutions and organisations dealing with consumer rights protection. The majority of surveyed consumers are not either interested in the use of collaborative consumption.